The Application of TGFU Learning in Volleyball Upper Passing Learning - Pratama, Andrias; Wardiah, Dessy; Junaidi, Ilham Arvan (Yayasan Sembilan Pemuda Indonesia, 2023)
TGFU (Teaching Game for Understanding) is game-centered learning and students learn games related to sports using a constructive approach. TGFU is a physical education learning model that uses elements of a tactical game without eliminating the technique with the aim of active movement for the development of skills and knowledge in teaching physical education. This tactic game learning model can increase students' interest and motivation in a game structure for developing skills and knowledge of volleyball upper passing techniques. Upper passing functions to form defense and attack because it is used to receive service, receive spikes, hit the ball that bounces off the net and most importantly to feed or give the ball to the smasher. The purpose of this study was to find out the application of TGFU (Teaching Game for Understanding) learning in volleyball upper passing learning. The method used in this research is literature review. Here, we will describe the relation to the application of TGFU learning in volleyball games, especially upper passing and the instruments commonly used to measure the upper passing ability. With the results of research from various sources, it can be concluded that the application of TGFU learning has a significant effect on upper passing on volleyball.